How do migrants from Latin America and the Caribbean fare in the US labour market? - Rivera-Batiz, Francisco L. (2007)
Presents the key trends in Latin America and Caribbean migration to the US, as well as the changes in the economic outcomes of the migrants over time. Provides a discussion of the factors that may explain the changes in the economic performance of these migrants when compared to other migrants. Presents estimates of the relative importance of these factors.